3x-(-7x+2)=x-2(6x+5)+(-2-9x)

Simple and best practice solution for 3x-(-7x+2)=x-2(6x+5)+(-2-9x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-(-7x+2)=x-2(6x+5)+(-2-9x) equation:


Simplifying
3x + -1(-7x + 2) = x + -2(6x + 5) + (-2 + -9x)

Reorder the terms:
3x + -1(2 + -7x) = x + -2(6x + 5) + (-2 + -9x)
3x + (2 * -1 + -7x * -1) = x + -2(6x + 5) + (-2 + -9x)
3x + (-2 + 7x) = x + -2(6x + 5) + (-2 + -9x)

Reorder the terms:
-2 + 3x + 7x = x + -2(6x + 5) + (-2 + -9x)

Combine like terms: 3x + 7x = 10x
-2 + 10x = x + -2(6x + 5) + (-2 + -9x)

Reorder the terms:
-2 + 10x = x + -2(5 + 6x) + (-2 + -9x)
-2 + 10x = x + (5 * -2 + 6x * -2) + (-2 + -9x)
-2 + 10x = x + (-10 + -12x) + (-2 + -9x)

Remove parenthesis around (-2 + -9x)
-2 + 10x = x + -10 + -12x + -2 + -9x

Reorder the terms:
-2 + 10x = -10 + -2 + x + -12x + -9x

Combine like terms: -10 + -2 = -12
-2 + 10x = -12 + x + -12x + -9x

Combine like terms: x + -12x = -11x
-2 + 10x = -12 + -11x + -9x

Combine like terms: -11x + -9x = -20x
-2 + 10x = -12 + -20x

Solving
-2 + 10x = -12 + -20x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '20x' to each side of the equation.
-2 + 10x + 20x = -12 + -20x + 20x

Combine like terms: 10x + 20x = 30x
-2 + 30x = -12 + -20x + 20x

Combine like terms: -20x + 20x = 0
-2 + 30x = -12 + 0
-2 + 30x = -12

Add '2' to each side of the equation.
-2 + 2 + 30x = -12 + 2

Combine like terms: -2 + 2 = 0
0 + 30x = -12 + 2
30x = -12 + 2

Combine like terms: -12 + 2 = -10
30x = -10

Divide each side by '30'.
x = -0.3333333333

Simplifying
x = -0.3333333333

See similar equations:

| 4+64y+256y^2=0 | | -56-8x=24-4x | | x/20=6/14 | | 10x+43=-32+5x | | (11x-23)= | | 4-12b+9b^2=0 | | 3*x-(-7*x+2)-(x-2*(6*x+5)+(-2-9*x))=0 | | 28n^2=-72-180n | | (10x+17)(7x-4)=0 | | 6x^2=-7x+20 | | 3x+130=-5x-102 | | 4/3•3.14•216 | | 7/12x3/4 | | 16x^2+16xy+y^2=0 | | -2k-5(k+6)= | | y=-x^2-8x+6 | | 2(3y-4)=(y-2/3) | | d/dx(e^(7lnx)) | | 9s^2-24s+16=0 | | 12z-8=52 | | (8x+13)= | | -3x+2(2x-6)=4(x-2)+2 | | -5+6(1-2n)= | | 87+0=87*n | | 12x+4=4x-20 | | (X-3)+30+80=180 | | h=-16t^2+70t+9 | | 4(5+a)-4a= | | -87=3(3-4n) | | (7c+4)(7c-4)= | | -8n+16n=-16 | | 40=1.3(x)+1.6 |

Equations solver categories